Real-space refinement of single-crystal electron diffuse scattering and its application to Bi(2)Ru(2)O(7-δ). - Goodwin, A; Withers, R; Nguyen, H (2007)
A real-space atomistic refinement approach to the analysis of experimental electron diffraction patterns is described. The method employs the reverse Monte Carlo algorithm to produce atomistic configurations capable of qualitatively reproducing diffuse electron scattering patterns. Its implementation in the program EDRMC is described in detail, together with a number of additional constraints/restraints that can be used to guide the refinement process. In particular, appropriate restraints ensure the individual atomic displacements introduced to model the diffuse scattering patterns are simultaneously consistent with the known average structure. The approach is then used to interpret electron diffraction patterns measured for Bi(2)Ru(2)O(7-δ). The diffuse scattering patterns observed are shown to arise primarily from concerted translations of Bi atoms. These translations can be interpreted in terms of rotations of [O(')Bi(4) ] tetrahedra correlated along the [Formula: see text] crystal axes and uncorrelated along orthogonal directions.